LAPAS ROKOK (LAMPU PENGHILANG ASAP ROKOK) BERBASIS FOTOKATALITIK NANOPARTIKEL ZnO - Milarsih, Yulia; Wibowo, Arif Sony; Wuning, Sri; Prasetya, Nor Basid Adiwibawa (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
ZnO is a photocatalyst essence that has economical value which can be able to degrade any dangerous organic compound by photocatalytic reaction. The purpose of this research is to fix any problems which are caused by smoke in Indonesia by innovation of smoke-disappeared light based on photocatalyst of ZnO nanoparticles. The zinc oxide (ZnO) has disadventage which can be initiated only by the UV light, so adding Co(Cobalt) is needed to decrease the gap-energy in order for it can work at visible light. The experiment method was carried out in three steps: (1) synthesis of ZnO nanoparticles by sol gel method, (2) the veneering was used the spray coating. The result showed that bandgap of ZnO which doped by Co is 2,28 eV, the size of nanoparticles which layered at the light-glass is about 40 nm, and can reduce CO until 3.69 ppm or 793,35 x 1019 particles for 10 minutes Keywords: LAPAS ROKOK, ZnO, nanoparticles, photocatalyst